Going in circles? The influence of the electoral cycle on the party behaviour in parliament. Issue 1 (5th February 2022) - Schwalbach, Jan
Abstract: Most analyses dealing with the interaction of parties in parliament assume their interests to be fixed between elections. However, a rational perspective suggests that parties adapt their behaviour throughout the legislative term. I argue that this change is influenced by incentives and possibilities to shape legislation and the need to distinguish oneself from competitors. While for government parties it matters whether they have to share offices, for opposition parties the influence on policy-making is important. By examining the sentiment of all parliamentary speeches on bill proposals from six established democracies over more than twenty years, I analyse institutional and contextual effects. The results show that single-party governments tend to become more positive towards the end of the legislative cycle compared to coalition governments. On the other hand, opposition parties under minority governments, or with more institutionalised influence on government bills, show a more negative trend in comparison to their counterparts.